2007
DOI: 10.1021/ci600205g
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Solubility Prediction with Error Bars for Electrolytes:  A Machine Learning Approach

Abstract: Accurate in silico models for predicting aqueous solubility are needed in drug design and discovery and many other areas of chemical research. We present a statistical modeling of aqueous solubility based on measured data, using a Gaussian Process nonlinear regression model (GPsol). We compare our results with those of 14 scientific studies and 6 commercial tools. This shows that the developed model achieves much higher accuracy than available commercial tools for the prediction of solubility of electrolytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 52 publications
1
83
0
1
Order By: Relevance
“…A good QSAR model not only has good summary statistics such as RMSECV and Q 2 , but also yields high stability of predictions for each sample. Several studies have indicated that the high stability of predictions of models correlates with the accuracy of predictions [63][64][65][66][67]. Thus, the standard deviation of prediction errors for each sample can be used as an additional metric characterizing the Fig.…”
Section: Ace Datamentioning
confidence: 99%
“…A good QSAR model not only has good summary statistics such as RMSECV and Q 2 , but also yields high stability of predictions for each sample. Several studies have indicated that the high stability of predictions of models correlates with the accuracy of predictions [63][64][65][66][67]. Thus, the standard deviation of prediction errors for each sample can be used as an additional metric characterizing the Fig.…”
Section: Ace Datamentioning
confidence: 99%
“…Furthermore, Gaussian Processes provides an estimate of uncertainty together with each prediction. Despite these strengths there have been only a small number of published examples of its application to QSAR and ADME modeling [5][6][7][14][15][16].…”
Section: Application Of Modeling Techniquesmentioning
confidence: 99%
“…Automatic model generation requires unsupervised computational techniques which do not require any input from a user, are able to deal with a large number of descriptors and are not prone to overtraining. In recent years, a variety of such modern modeling techniques have been applied to QSAR modeling; some examples include Bayesian Neural Networks [3], Associative Neural Networks [4] and Gaussian Processes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Models encode relationships between molecular structure and properties, but interpreting and visualising this information to design better molecules has been almost impossible. This is particularly true of models built with modern machine learning techniques such as artificial neural networks [5], Gaussian processes [6] [7], Fig. 3.…”
mentioning
confidence: 99%